The pressure field associated with a spherical diffusion flame - Cooper, C. A. (Cranfield Institute of Technology, 1975)
The pressure field associated with a spherically symmetric diffusion flame is studied. The flame itself is described using the Lurke-Schumann infinitely-thinflame- sheet model and the associated pressure field is analysed using the method of inner and outer expansions. Rapid pressure variations are found to be present in the regions close to the flame sheet.